Analisis Faktor-Faktor Yang Mempengaruhi Struktur Permodalan Emiten Perbankan Yang Terdaftar di BEI - Chaidir Achmad; Haspul Naser; Nurwulan Kusuma Devi; Meirna Milisani; Ratnawita Ratnawita (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
PT. Bank Central Asia (BCA) is a company engaged in Banking Services and has a variety of products and services such as; Savings Products, Credit Cards, Credit Facilities, Banking Transaction Services, Cash Management Services, Bancassurance, Bank Guarantees, Export Import Facilities, Foreign Exchange Facilities and Electronic Banking. BCA experienced fluctuations in Return On Assets (ROA), Asset Structure Variables, and Capital Structure Variables (DER) in Quarters 1, 2,3, and 4. From 2014 to 2021, Variable Size increased in succession from 2014 to 2021. Research Objectives : Analyzing the effect of Profitability (Return On Assets) on Capital Structure (DER), Asset Structure on Capital Structure, Company Size (Size) on Capital Structure (DER), and Profitability (Return On Assets (ROA), Asset Structure and Company Size ( Size) jointly affects Capital Structure (DER). Novelty (Novelty): Based on several previous studies, several factors whose results are inconsistent so need to be reviewed. The author chooses Profitability (ROA), Asset Structure, and Company Size as independent variables , which affects Capital Structure as the dependent variable Research Methods: The data analysis method used in this study is multiple linear regression analysis and uses an SPSS 23 software for windows Conclusion: BCA can generate sufficient profit to finance its operations, and does not need to increase the amount of debt so as to prioritize internal funding through retained earnings and maintain a low debt ratio. In addition, companies must balance the benefits of using debt and the costs incurred to achieve an optimal capital structure.Keywords— Asset Structure, Company Size, Capital Structure, andReturn On Assets